15.6k views
0 votes
Please help me answer this!!

Please help me answer this!!-example-1

1 Answer

6 votes

Answer:

x = 3, x = 6

Explanation:

Using the rules of logarithms

log x - log y = log (
(x)/(y) )

log
x^(n) ⇔ nlog x


log_(b) x = n ⇔ x =
b^(n)

Given

2
log_(3) x -
log_(3)(x - 2) - 2 = 0 ( add 2 to both sides )


log_(3) x² -
log_(3)(x - 2) = 2


log_(3) (
(x^2)/(x-2) ) = 2


(x^2)/(x-2) = 3² = 9 ( multiply both sides by x - 2 )

x² = 9(x - 2) ← distribute

x² = 9x - 18 ( subtract 9x - 18 from both sides )

x² - 9x + 18 = 0 ← in standard form

(x - 3)(x - 6) = 0 ← in factored form

Equate each factor to zero and solve for x

x - 3 = 0 ⇒ x = 3

x - 6 = 0 ⇒ x = 6

User Swiss Frank
by
6.4k points